Learning Management System Design Course And Training Institutions (Case Study: Earth Creative Institute) - Cecep Kurnia Sastradipraja; Dery Ahmad Kamalino; Falentino Sembiring (Unversitas Muhammadiyah Mataram, 2020)
Abstract: This research aims to design a learning management system application at LKP Bumi Kreatif Institute where the learning process in the institution is still classically carried out and does not have system support for online learning so that learning will be hampered in the event of natural disasters such as the Current Covid-19 pandemic because it requires all learning activities to be carried out at home and there is no direct interaction between students and instructors in the classroom. The process in developing applications using waterfall models includes observation studies, system modeling using UML, application construction using PHP and MySQL programming languages as database management, system testing using BlackBox, and to test application feasibility, usability testing is used by distributing questionnaires and weighting through Likert scales. Based on the results of research conducted that the application built can be implemented and able to facilitate online learning activities at the LKP Bumi Kreatif Institute, starting from the registration process, payment calculation, course administration management, students, and instructors. The results of the usability value recap show the overall attribute has an average user acceptance value of 4.27 so it can be said that the application implementation of Learning Management System in LKP Bumi Kreatif Institute has a good value of usability aspect, namely: learnability, efficiency, memorability, errors, and satisfaction.Abstrak: Penelitian ini bertujuan untuk merancang aplikasi sistem manajemen pembelajaran di Lembaga LKP Bumi Kreatif dimana proses pembelajaran di lembaga tersebut masih dilakukan secara klasikal dan belum memiliki dukungan sistem pembelajaran daring sehingga pembelajaran akan terhambat jika terjadi bencana alam seperti pandemi Covid-19 saat ini karena mengharuskan semua kegiatan pembelajaran dilakukan di rumah dan tidak ada interaksi langsung antara siswa dan instruktur di dalam kelas. Proses dalam pengembangan aplikasi menggunakan model waterfall meliputi studi observasi, pemodelan sistem menggunakan UML, pembuatan aplikasi menggunakan bahasa pemrograman PHP dan MySQL sebagai pengelolaan database, pengujian sistem menggunakan BlackBox, dan untuk menguji kelayakan aplikasi digunakan pengujian usability dengan menyebarkan kuisioner dan pembobotan melalui Skala likert. Berdasarkan hasil penelitian yang dilakukan bahwa aplikasi yang dibangun dapat diimplementasikan dan mampu memfasilitasi kegiatan pembelajaran daring di lembaga LKP Bumi Kreatif, mulai dari proses pendaftaran, perhitungan pembayaran, pengelolaan administrasi kursus, mahasiswa, dan instruktur. Hasil rekap nilai usability menunjukkan secara keseluruhan atribut memiliki rata-rata nilai penerimaan pengguna sebesar 4.27 sehingga dapat dikatakan bahwa penerapan sistem manajemen pembelajaran di LKP Bumi Kreatif Institute memiliki nilai aspek usability yang baik yaitu: learnability, efficiency, memorability, errors, and satisfaction.